Tingkat Kecemasan pada Ibu Hamil selama Pandemi Coronavirus Disease 2019 - Azwar Asy'ari Fahruddin; Mateus Sakundarno Adi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
The Coronavirus-2019 (Covid-19) pandemic is spreading across the globe. Indonesia is one of the countries worst affected by COVID-19. The COVID-19 pandemic has raised serious concerns including anxiety in pregnant women. Mental and physical changes during pregnancy, pregnant women are most likely to be exposed to the virus. The purpose of this study was to assess the level of anxiety and related factors during the COVID-19 pandemic in pregnant women. This study method was a literature review of electronic data such as Google Scholar, Science Direct, Pubmed and selected 5 articles published in 2020. The results of this literature review study indicated that the corona virus pandemic has a significant psychological impact on the mother's physiological state. Covid-19 has been shown to greatly affect the level of maternal anxiety during pregnancy during this pandemic. Excessive anxiety can adversely affect the health of the fetus. The length of time during isolation, quarantine, national lockdown, gestational age, lack of information related to COVID-19, low education are factors that affect the level of maternal anxiety during pregnancy. Keywords: anxiety; pregnant mother; covid-19; coronavirus disease 2019 ABSTRAK Pandemi Coronavirus-2019 (Covid-19) menyebar di seluruh dunia. Indonesia termasuk salah satu negara yang paling parah terkena dampak covid-19. Pandemi covid-19 telah menimbulkan kekhawatiran serius termasuk kecemasan pada ibu hamil. Perubahan mental dan fisik selama kehamilan, ibu hamil kemungkinan besar akan terkena virus tersebut. Tujuan penelitian ini untuk menilai tingkat kecemasan dan faktor-faktor terkait selama pandemi covid-19 pada ibu hamil. Metode studi ini adalah literature review dari data elektronik seperti Google Scholar, Science Direct, Pubmed dan terpilih 5 artikel yang dipublikasikan tahun 2020. Hasil penelitian literatur review ini menunjukkan bahwa pandemi virus corona memiliki dampak psikologis yang signifikan terhadap keadaan fisiologis ibu. Covid-19 terbukti sangat berpengaruh terhadap tingkat kecemasan ibu saat hamil dimasa pandemi ini. Kecemasan yang berlebihan dapat berpengaruh buruk terhadap kesehatan janin. Lamanya waktu saat isolasi, karantina, lockdown nasional, usia kehamilan, kurangnya informasi terkait covid-19, pendidikan yang rendah merupakan faktor yang berpengauh terhadap tingkat kecemasan ibu saat hamil. Kata kunci: kecemasan; ibu hamil; covid-19; coronavirus disease 2019